PREDICTING THE INCREASE OF COMPANY VALUE BASED ON PROFIT AND DEBT GOVERNANCE POLICIES: A Case Study on Indonesian Automotive Companies - Solahudin, Muhamad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
For large companies that have gone public, corporate values ​​are highly guarded and considered important. Because, the company is aware of the impact generated by the value of the company, namely the ease of obtaining investment funds. Due to the large benefits of corporate value for future business development on a large/global scale, various efforts have been made to maintain and continue to increase corporate value. Based on this point of view, this research was conducted to predict the increase in company value based on earnings and debt governance policies. The research method uses a quantitative approach and data is analyzed using linear regression. The research object is an Indonesian automotive company with financial report data as a research sample. The financial statements used are 11 data with purposive techniques. The results of the study show that the policy of controlling debt and profits directly affects the company's financial strength, and this has an impact on the income earned by investment. These conditions, have a positive impact on public assessment, which then increases the value of the company.